(untitled) (Al-Mansour Journal, 2022)
The study aimed to illustrate factors affecting planning of the educational policy for bachelor in Accounting program that offered in the accounting and finance department in the faculty of business at MEU to attain performance efficiency and effectiveness. In the study, it is realized that the accounting department is one of the most important departments of the collage for number of students, faculty members and classes; it is also declared that factors affecting the department’s performance are the students, faculty members, study plan, department’s leader, faculty deanship, and the university’s vision. Planning the educational policy of the program succeeds if all of its interrelated six elements studied will. The study suggest many recommendations that may help program success, some of which are: it is not enough to fulfill the accreditation requirements, the university has to staff qualified academic and administrative staff, study plan has to be modernized, as well as diversifying teaching ways.